The Transformation of Qur'an Literacy Through the Tahfidz Method: An Experimental Study on Elementary School Students - Yugo, Tri; Surana, Dedih; Muhammad, Giantomi; Pamungkas, Muhamad Imam (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The Tahfidz method strategically improves students' Qur'an literacy, especially in tajwid, fluency, and memorization. This study aims to evaluate the effectiveness of the Tahfidz method in increasing the memorization capacity of the Qur'an of grade 6 students of SDN Jatimekar through a pseudo-experimental approach with a Nonequivalent Control Group Design. 72 students were divided into an experimental group (Tahfidz method, n=36) and a control group (conventional method, n=36). The results of the t-test showed a significant difference between the average final test score of the experimental group (82) and the control group (78), with t(70) = 4.094, p < 0.05. The Tahfidz method has been proven to significantly increase the memorization capacity of the Qur'an, especially in the application of Tajwid and fluency in reading. The study offered novelty through the correlation of the intensity of the Tahfidz method with the improvement of students' abilities, showing a significant positive relationship (r = 0.917, p < 0.05). The implications of this research include integrating the Tahfidz method in the curriculum, teacher training for the effective application of methods, and using technology such as gamification to overcome time constraints and student motivation. This research makes an important contribution to the development of national Qur'an literacy and becomes a practical reference for educators and policymakers to improve the quality of Islamic religious education.